Prevalence of Liver disorders in Islamabad City - Toor, Sabeen; Toor, Sidra; Ashraf, Asfa; Alam, Saman; Anwaar, Samavia; Saddiqa, Ayesha; Ali, Shahzad; Toor, Samra; Muhammad, Ali; Akhter, Shamim (PSM Biological Research, 2016)
The purpose of this study was to determine the prevalence of liver disorders through liver function enzyme tests (LFTs) in Islamabad. A total of 250 blood samples were screened in Kahuta Research Laboratory (KRL), Islamabad for the presence of liver disorders through liver function enzyme tests (LFTs) viz., alanine aminotransferase (ALT), Total Bilirubin (T.Bil) and alkaline phosphatase (ALP). The results were analyzed by comparing the correlation among ALT, ALP and T. Bilirubin and compiled by comparing elevated level of LF enzymes with respect to age. It has been observed that correlation coefficient between ALT and T. Bilirubin; ALP and T. Bilirubin; ALT and ALP was positive values which indicate that slightly elevation in these enzymes released from hepatocytes cause liver disorders. The level of ALT and ALP abruptly decreased in (1-15 years), and then it gradually increased in age groups 16-30 years, 31-45 years. Their level was much higher in (46-60 years). However the level of T. Bilirubin was higher in children and adults in age groups (1-15years) and (46-60 years) but it was slightly elevated in age groups (16-30 years) and (31-45 years). It is concluded that elevation of liver enzymes is responsible for liver disorders.